FC 007CKD DERIVED MUSCLE CELLS RETAIN PHENOTYPIC CHARACTERISTICS OF UREIC SARCOPENIA: THE NEXT STEP IN CELLULAR MODELLING FOR THERAPEUTIC SCREENING. (29th May 2021) - Baker, Luke; O'Sullivan, Thomas; Robinson, Kathrine; Graham-Brown, Matthew; Ashford, Robert; Smith, Alice; Watson, Emma
Abstract: Background and Aims: Skeletal muscle wasting and dysfunction is a debilitating co-morbidity for people who suffer from kidney disease. To date research has sought to understand the mechanisms by which this occurs, in order to inform the prescription of required interventions in order to counteract such effects. Though progress has been made through in-vivo physiology research, the lack of an in-vitro translational model which replicates the phenotype noted in this patient group has hindered progression. The aim of the work presented was to systematically define a human derived skeletal muscle model with cells derived from people with kidney disease, in order to provide a test bed for the future screening of novel therapeutics and the investigation of the dynamic processes involved in the unwanted characteristics observed in this population. Method: Skeletal muscle biopsies were taken from the vastus lateralis of non-dialysis dependent CKD patients (CKD; n=12) and Controls (CON; n=12), matched for age, sex, ethnicity and physical activity levels. Biopsy samples were subject to an enzymatic digestion method to enable the isolation of the muscle derived cells required for cellular experimentation. Once taken through the cell cycle, cells were plated into experimental wells and proliferated for 5 days or until confluent. Once confluent cells were differentiated through serum restriction to form mature myotubes (muscle fiber like structures) for a minimum of 7 days. Sampling time points were taken throughout to allow for the analysis of markers of proliferation, myogenic capacity, maturation, inflammation, protein synthesis and protein degradation. Further experiments were conducted on mature myotubes, where myotubes from both donor groups were exposed to either 0.4nM or 100nM of IGF-1 and p-Akt and protein synthesis quantified to investigate the presence of anabolic resistance in CKD derived cells. Results: We report here that muscle cells derived from CKD patients have significantly higher levels of markers of proliferation (p = 0.041) and myogenic capacity (p = 0.034). Regarding myotube maturity, lower ratios of mature Myosin Heavy Chains were noted in CKD derived cells in comparison with CON derived cells (p = 0.012). On analysis of rates of protein synthesis and degradation in mature myotubes, no differences were noted in the rate of protein synthesis or the p-Akt in basal conditions (p > 0.05), however, significant elevations were noted in both protein degradation rates (p = 0.014) and the mRNA gene expression levels of E3-ligases (p = 0.016). On analysis of the experimentation investigating anabolic resistance, a degree of anabolic resistance was noted with inhibited p-Akt (p = 0.019) and protein synthesis (p ≤ 0.001) noted in cells derived from CKD cells in comparison to CON cells, when exposed to both doses of IGF-1. Conclusion: Here we describe for the first time a human derived, disease specific model of uremic sarcopenia with many of the phenotypic traits noted in this population being maintained, such as elevated protein degradation and anabolic inhibition. This work not only provides a translational mechanistic insight into the cellular underpinnings of uremic sarcopenia but will allow for the future screening of novel therapeutics, in order manipulate the dynamic processes which lead to the debilitations noted in CKD populations.